Child Care for Parents Works in Human Rights - Cindy Audiya Ajizi; Wiwik Afifah (Journal of International Trade, Logistics and Law, 2024)
Child care places in Indonesia are very much needed for working parents. The availability of child care places is a form of the state's obligation to fulfill the rights of its citizens. The absence of regulations regarding child care for working parents is one of the problems that can hinder both working parents and children's growth and development. This research uses normative juridical and empirical juridical research methods which use a statutory approach, a conceptual approach and a legal sociology approach. Human Rights are based on universal principles such as dignity, equality, freedom and justice. Human Rights aims to protect and respect the basic rights of every individual without regard to race, religion, sex, color, language, political opinion, national or social origin, property, birth, or other status. This is considered a right inherent in humans from birth and cannot be taken away. The same is true with the right to obtain care for children and also the right to obtain work for parents. These two rights are in conflict because there is no means to fulfill the necessary rights for children and parents. To exercise these rights, the state is obliged to provide child care which is the answer to obstacles that arise in the household and work sectors.